(3TQM bGfhf efY GdLQGFe (B/s - (3GdHUhd, YeQ eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2010)
(3dgPG GdbGfhf ef CgejI hNWhQI cHjQJjf ef MjK GdJWHjb, hPdc Cfg jJUGOe hjJOGNd, dG Hd hjdZj GdbhGfjf GdLRGFjI GdOSJhQjI (B((3bGfhf GdYbhHGJ, hbGfhf CUhd GdeMGceGJ GdLRGFjI(B) (3GdJj JWHbgG GdeMGce GdfXGejI UGMHI GdGNJUGU hGdhdGjI GdYGeI aj fXQ LejY GdefGRYGJ hGdOYGhi HebJVi fUhU hbhGYO GdOSJhQ (B((3GdbGfhf GdCYdi(B) (3hGdJj fUJ Ydi VeGfGJ ddSdWI GdbVGFjI, hcadJ dgG GdMeGjI ef GdJONd aj TDhfgG, ceG hfUJ Ydi VQhQI JfXje GdeMGce hMeGjJgG(B. (3hbO Sf GdeTQY GdCQOfj eLehYI bhGfjf NGUI JMbjbG dgPg GdZGjI hGeJKGdG dbhGYO hCMcGe GdOSJhQ(B. (3hgPg GdbhGfjf (B: (3bGfhf GSJbdGd GdbVGA, hbGfhf JTcjd GdeMGce GdfXGejI(B. (3EdG Cf bGfhf efY GdLQGFe de jMJQe fUhU hbhGYO gPg GdbhGfjf GdOSJhQjI, hde jMJQe fUhU hbhGYO GdOSJhQ CjVG, hJLGhRgG hYWdgG hCdZGgG aj cKjQ ef GdCMjGf, hPdc HCf CYWi GdMGce GdEOGQj UdGMjGJ hGNJUGUGJ hSdWGJ bVGFjI dG Hd hCYWGg GdMb aj EfTGA eMceJg GdNGUI Hg, ceG hCYWGg GdMb aj eMGceI GdCTNGU GdeMVQjf CeGeg HebJVi bGfhf efY GdLQGFe hEUOGQ GdCMcGe HMbge MJi dh de jQJcHhG CaYGdG jLQegG GdbGfhf hjYGbH YdjgG, Ch MJi HYO UOhQ Mce bVGFj HMbge Yf GdeMGce GdfXGejI GdOSJhQjI UGMHI GdGNJUGU hGdhdGjI GdYGeI aj EUOGQ GdCMcGe GdbVGFjI, hGdPj ZGdHG eG jchf HYOe eSFhdjJge Ch HefY eMGceJge Ch HHQGAJge(B.s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdCfJGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B187-192.s
Keywords: (3GdbGfhf GdLfGFjs -- (3GdCQOfs; (3GdLQjeI hGdeLQehfs -- (3GdCQOfs